Patterns of single nucleotide polymorphism (snp) variation: further insights into the complex history of the iberian honeybee - Pinto, M. Alice (2013)
The Iberian Peninsula harbours the greatest honeybee genetic diversity and complexity in Europe. The challenge of deciphering the mechanisms underlying such complexity has led to numerous morphological and molecular marker-based surveys of the Iberian honeybee. Yet, in spite of the numerous studies, the evolutionary processes underlying patterns of Iberian honey bee genetic diversity remain poorly understood. Early phylogeographical studies of morphology and allozymes revealed the existence of a gradient extending from Africa to northern Europe, with Iberian honeybees showing intermediate phenotypes. This pattern raised the hypothesis of an African origin and a mechanism of primary intergradation for the Iberian honeybee (and the black honeybee) origin. Maternal patterns tell a different history. Mitochondrial DNA (mtDNA) surveys have revealed the co-occurrence of highly divergent lineages forming a south-north cline, a pattern that is more compatible with a recent secondary contact hypothesis. Adding to the complexity, microsatellite variation supports neither hypothesis as microsatellites showed virtually no differentiation and no traces of African genes in Iberian honeybees. In an attempt to resolve this debate we recently performed a fine resolution (both geographic and genomic) survey of the Iberian honeybee using SNPs, genotyped using automated high throughput technologies of Illumina, and mtDNA sequencing data of the tRNAleu-cox2 highly polymorphic region. The dataset was analyzed using a battery of methods implemented by the programs ARLEQUIN, STRUCTURE, ADEGENET, TESS, BAYESCAN, among others. The results were interesting: contrasting with microsatellites, SNPs were able to recover the clinal signal in the Iberian Peninsula producing a spatial pattern that was concordant with mtDNA. However, the differentiation levels within Iberian populations and between Iberian and northern African populations do not support a recent secondary contact. Herein, the results of the SNP surveys will be presented and new hypotheses will be discussed.